FINANCIAL RISK AND RATING INVESTMENT GRADE ALTMAN STUDY : ISSUER OF FOOD AND BEVERAGES - Ambardi Ambardi; Aam Aminah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
ABSTRAKThis study was conducted to analyze the company's risk in terms of financial risk and its effect on the investment rating. While the analytical method to measure the health of a company or company in a safe condition (no risk) is to use the Altman investment grade rating model. While the financial risk used in this study is measured by the current ratio and debt to asset ratioThe formulations in this study are: How the Current Ratio (CR) affects the Investment Value Rating of food and beverage issuers, how the Debt Asset Ratio (DAR) affects the Investment Rating Rating of food and beverage issuers.This research is a descriptive research with a quantitative approach. While the population of this study is all food and beverage sub-sectors listed on the Indonesian stock exchange for the period 2016 – 2020. The sampling technique used in this study is the purposive sampling method.Testing the analysis in this study using logistic regression because the dependent variable is measured using a dummy variable. Test analysis with logistic regression was carried out as follows; First, select the Regression Model using Hosmer and Lemeshow's Goodness of Fit Test. Second, the Summary Model with R2 test on linear regression. Third, Partial Test (Hypothesis) to test the significance of the regression/partial coefficient, which is used to determine the partial effect between the independent variables and by looking at the probability of sig at a significance level of 5%.The conclusion of this study is that the variable current ratio and Debt to Asset ratio have a significant effect on Altman's investment grade rating on food and beverage issuers. Furthermore, the current ratio and debt-to-asset ratio variables can be used to assess the level of risk faced by investors in choosing safe issuers Keywords: Financial Risk, Investment Grade Rating, Food and Beverage